Influence of Cr Doping on Structural, Optical, and Photovoltaic Properties of BiFeO3 Synthesized by Sol-Gel Method - José Tiburcio; Elisban Sacari; Jesús Chacaltana; Jesús Medina; Francisco Gamarra; Carlos Polo; Efracio Mamani; Alberto Quispe (Energies, 2023)
In this work, pure BiFeO3 and samples doped with different concentrations of chromium were synthesized to improve the optical properties and efficiency of solar cells based on BiFeO3. The sol-gel method was used for synthesis due to its ability to produce nanostructured materials with high purity and good homogeneity, as well as the possibility of controlling the size and shape of the resulting particles. The samples were characterized by different analytical techniques. Thermal analysis results indicate that the dopant increases the weight loss of the sample from 61 to 81%, with an increase in the exothermal in the nucleation and crystallization temperature range. The X-ray diffraction patterns and UV-visible spectra show a dependence of the crystallite size and bandgap with respect to the amount of Cr dopant, decreasing from 168 to 73 nm and from 2.14 to 1.92 eV, respectively. Scanning electron microscopy images display a decreasing grain size as a result of an increasing amount of dopant. The I-V analysis results show a 1% Cr-doped BiFeO3 photovoltaic device exhibits enhanced photovoltaic performance with higher photocurrent and 4.17 times greater energy conversion efficiency compared with a pure BiFeO3 photovoltaic device. For their behavior, Cr-doped BiFeO3-based photoelectrodes are very promising materials for photovoltaic devices.